Modeling and Simulation Longitudinal Mobile Robotic with Rough Terrain and Ascent Angle Disturbance - Emilliano, Emilliano; Hindersah, Hilwadi (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
Model mobile robot that used to this simulation is type car like vehicle steering. Mobile robot type car like vehicle steering is mobile robot that move using force of rear wheel and front rear of mobile robot functions as steering to control direction of mobile robot. The dynamic nonlinear model mobile robot is implemented to view influence disturbance of mobile robot to longitudinal direction mobile robot that used to planetary exploration in rough terrain. The model that used to simulation is nonlinear multivariable MIMO with 5 input and 7 output. The simulation has done by using Simulink of Matlab. The simulations were carried out by giving 4 conditions, namely without disturbance, with an incline angle of 30 (0.5236 rad), with a rough terrain angle of 28.6479 (+0.5 rad), and a combination of 30 incline angle and 28.6479 rough terrain angle. The simulation results with 3 mobile robots show accurate results.